Optimal Management and Delivery Time for Intrahepatic Cholestasis of Pregnancy: Meta-analysis [37D]. (May 2017) - Savasan, Zeynep Alpay; Zeb, Amna
Abstract : INTRODUCTION: To determine the risk of adverse perinatal outcomes in patients with intrahepatic cholestasis of pregnancy (IHCP) with gestational age at delivery and treatment modalities. METHODS: A systematic search of MEDLINE, EMBASE, Web of Science and Cochrane Central Register of Controlled Trials was performed. The inclusion criteria consisted of randomized controlled clinical trials (RCTs) consisting of ursodeoxycholic acid (UDCA) compared with other treatments like placebo, dexamethasone, cholestyramine and SMAe for IHCP. RESULTS: 11 RCTs were eligible for analysis. Data was analyzed on 542 patients, of which 281 received UDCA and 261 received other treatments. Use of UDCA delayed gestational age at delivery by 6 days {SMD=0.59 (95% CI: 0.08-1.09); p < 0.001}. Risk for preterm delivery and NICU admission decreased in group treated with UDCA compared to other treatments {RR=0.52 (95% CI: 0.38-0.72); p < 0.001 and RR=0.53 (95% CI: 0.29-0.97); p=0.038}, respectively. Risk of adverse perinatal outcomes was decreased for delivery at 36 weeks {RR=0.59 (95% CI: 0.39-0.90); p=0.013} compared for delivery at 37 weeks. UDCA treatment decreased the risk of meconium staining and c-section with increased birth weight but these results did not show statistical significance. CONCLUSION: Treatment choice of IHCP should be UDCA and 36 weeks appeared to be the optimal time of delivery.[ZERO WIDTH SPACE]